Recombinant expression, purification and in vitro interaction analysis of HOP and RhoC - Vaaltyn, Michaelone Chantelle (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2016)
Expected release date-May 2019
Keywords: Uncatalogued